2017
DOI: 10.1117/12.2269379
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive control of influence of polyethylene glycol on transport function of fluorescent colored liposomal nanoparticles

Abstract: invasive control of influence of polyethylene glycol on transport function of fluorescent colored liposomal nanoparticles,"

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…The similar result by the same probe was obtained by the authors for liposomal particles in previous studies. 8,9 The diagnostic volume and depth for the fluorescence measurements for the different excitation wavelengths for the fiber optical probe were also assessed by the Monte Carlo modelling previously. 16 Based on the results of the study, it was found that the nanocapsules contribute to the distribution and accumulation of the dye in tissue.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The similar result by the same probe was obtained by the authors for liposomal particles in previous studies. 8,9 The diagnostic volume and depth for the fluorescence measurements for the different excitation wavelengths for the fiber optical probe were also assessed by the Monte Carlo modelling previously. 16 Based on the results of the study, it was found that the nanocapsules contribute to the distribution and accumulation of the dye in tissue.…”
Section: Resultsmentioning
confidence: 99%
“…The diagnostic approach has considerable potential for drug discovery, not only during the development of a new drug formula but also in preclinical and clinical trials. 8,9 Optical methods, in particular, fluorescent spectroscopy, are promising tools for diagnostics in the modern medical practice as well 10 . Another vibrant area of modern study is targeted delivery of medicines, which can significantly improve the effectiveness of treatment of various diseases, reduce the occurrence of possible adverse side effects and disease complications.…”
Section: Introductionmentioning
confidence: 99%